IBRAH AND MAW'IZAH METHOD: Looking at the Actualization of Islamic Education Learning in Schools - Kurniawan, Muhammad Rafiq (Tsaqofah : Jurnal Pendidikan Islam, 2021)
The ibrah-maw'izah method is often referred to as the advice method, which is a method of education and also teaching by means of educators providing motivation. The ibrah-maw'izah method is very effective in the process of forming aqidah and akhlaq, as well as motivating them to be noble, and equipping them with Islamic principles and values. According to the Qur'an, the method of advice is given to those who have violated the rules and regulations in the sense that when a truth has reached them, it is as if they do not want to know the truth, let alone implement it. The ibrah-maw'izah method is a method of delivering PAI learning material through a speech process that contains advice and warnings about the good and bad of a case. Furthermore, the conclusions of this study related to the ibrah-maw'izah method are: First; Among the approaches taken by the teacher, namely by using a rational approach, a direct approach, and an indirect approach. Second; the ibrah-maw'izah method can be applied with good learning and advice methods, bi al-mauizhah al-hasanah, the language and meaning of symbols, addresses, signs, promises, guides, instructions, and satisfying arguments through soft speech full of love, tenderness of heart that can touch the soul. Third; fostering obedience to God's commands through the practice of worship to children in the family environment and also providing advice for those who do not have good personalities. Keywords: The ibrah method, the maw'izah method, and PAI learning